2006
DOI: 10.1007/s11145-006-9003-4
|View full text |Cite
|
Sign up to set email alerts
|

Explicit instruction in orthographic structure and word morphology helps Chinese children learn to write characters

Abstract: Previous research in alphabetic languages had shown that children learning to write are sensitive to morphological information, and that it serves as a resource that they draw upon as they acquire writing skills. In Chinese as well, sensitivity to morphological and orthographic information had been found to predict children's ability to read characters. The present study investigated whether raising children's awareness of the morphemic and orthographic structure of Chinese words would lead to beneficial resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 38 publications
5
87
0
Order By: Relevance
“…These errors can be minimized and the quantity and precision of derived words can be increased with appropriate training in orthographic and morphological structure of Chinese words. The study by Packard et al (2006) carried out with Chinese first graders has shown the beneficial effect of explicit training in morpheme discrimination and morpheme transfer on Chinese character writing.…”
Section: Discussionmentioning
confidence: 99%
“…These errors can be minimized and the quantity and precision of derived words can be increased with appropriate training in orthographic and morphological structure of Chinese words. The study by Packard et al (2006) carried out with Chinese first graders has shown the beneficial effect of explicit training in morpheme discrimination and morpheme transfer on Chinese character writing.…”
Section: Discussionmentioning
confidence: 99%
“…As Packard et al (2006) observed, reading and writing might be associated without having a causal relationship, instead linked through some third variable, such as cognitive ability (e.g., orthographic knowledge, phonological memory, etc. ), which affects both skills independently.…”
Section: Evidence For Writing Effects In Chinesementioning
confidence: 96%
“…A series of studies conducted in Mainland China and Hong Kong showed that children's morphological awareness, including the ability to distinguish among meanings of homophones and morpheme construction skills, contributed significant amount of unique variance to Chinese word reading, word spelling and reading comprehension over and above phonological processing skills (McBride-Chang et al, 2003;Shu et al, 2006). Moreover, explicit instruction in the morphological structure of Chinese words was effective in enhancing children's ability to write characters (Packard et al, 2006).…”
Section: Skills Important To Word Reading In Chinesementioning
confidence: 99%